Зменшення шумів і завад шляхом раціонального вибору електронних компонентів в каналах з зосередженими параметрами при високошвидкісній обробці даних - Tynynyka , Oleksandr (PE "Politekhperiodika", Book and Journal Publishers, 2019)
When designing most electronic systems, the main focus is on the development of the devices themselves, while the problem of meeting the requirements for the interference protection usually take second place, which calls for a need in this particular study.The article is devoted to methods and rules for design of radio electronic devices, which reduce noise and interference. The author provides practical guidance in the issues of choosing components, installing cables and connectors, designing print nodes and interference filtering. The urgency of these tasks is caused by several principal reasons, i.e., the increase of the speed of semiconductor devices and electronic circuits in general, reducing the amplitudes of the working signals of digital devices, increasing effect of interconnects and cascade layouts on the stability and speed of electronic devices and systems, the complex, costly and time consuming process of finding and eliminating the causes of low noise immunity of electronic devices.With the speed growth and the layout density of the elements, ensuring the noise immunity of the electromagnetic interaction between different devices and systems becomes the most important task of designing the radio electronic systems in general. When designing any electronic circuit, additional resistive, inductive and capacitive parasitic parameters are inevitably introduced. This can critically affect the performance of the real-life design by lowering its speed and noise immunity, even leading to complete failure. Design and installation have a particularly strong influence on the operation of high-speed (high-frequency) circuits and devices. In such cases, system speed, noise immunity and electromagnetic compatibility become the main criteria for the quality of electronic design.